2022
DOI: 10.1530/ec-22-0303
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab in the treatment of Graves’ orbitopathy: latest updates and perspectives

Abstract: Graves’ orbitopathy (GO) is a potentially sight-threatening and disfiguring, extrathyroidal manifestation of Graves’ disease. It often impairs patients’ quality of life, causing severe social and psychological sequelae. Intravenous glucocorticosteroids is currently the mainstay of therapy but the efficacy is often underwhelming and recurrence rate is high. For many years clinicians have been searching for new methods of treatment. Rituximab (RTX), a chimeric monoclonal antibody targeted against CD20 which is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 62 publications
0
3
0
1
Order By: Relevance
“…The promising results of RTX in GO were first reported in 2006 ( 25 ), and since then several studies have shown significant improvement in CAS with low relapse rates after RTX infusion ( 67 , 68 ). However, in 2015, two RCTs of 25 and 32 patients with GO showed conflicting results, raising concerns about the benefit of RTX in GO ( 26 , 30 , 32 , 69 , 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…The promising results of RTX in GO were first reported in 2006 ( 25 ), and since then several studies have shown significant improvement in CAS with low relapse rates after RTX infusion ( 67 , 68 ). However, in 2015, two RCTs of 25 and 32 patients with GO showed conflicting results, raising concerns about the benefit of RTX in GO ( 26 , 30 , 32 , 69 , 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…В целом в обеих группах титр АТ-рТТГ уменьшился примерно на 15% [28]. Вместе с тем не во всех исследованиях регистрировался подобный эффект [29,30]. Проведенный метаанализ 12 исследований с включением 152 пациентов с ЭОП, которым внутривенно был введен РТМ, продемонстрировал ограниченный эффект последнего на экзофтальм, однако было отмечено статистически значимое снижение тит ра АТ-рТТГ после 6-го и 12-го месяца наблюдения [31].…”
Section: результаты основных исследованийunclassified
“…Rituximab (RTX) is a human/murine chimeric anti-CD20 monoclonal antibody [ 8 ] that leads to B-cell depletion via various mechanisms, including antibody-dependent and complement cytotoxicity, alterations in intracellular calcium and apoptosis [ 9 ]. It is mainly used to treat CD20 + B-cell lymphomas but is also involved in the treatment of autoimmune diseases, such as lupus erythematosus or rheumatoid arthritis [ 10 ]. RTX is now recommended as a second-line treatment for active moderate-to-severe GO.…”
Section: Introductionmentioning
confidence: 99%
“…B lymphocytes and anti-thyrotropin receptor antibodies play important roles in this process [ 2 ]. Given the suppressive effect of RTX on B cells and autoimmunity [ 10 ], we hypothesized that RTX could be used to treat DON. Therefore, our study aimed to investigate the efficacy of 500 mg RTX as a second-line treatment for steroid-resistant GO in a single Chinese institution, with an emphasis on the treatment responses of patients with DON.…”
Section: Introductionmentioning
confidence: 99%